2023
DOI: 10.3390/en16093613
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Sustainability: The Role of Digitization in Re-Inhabiting the Existing Building Stock

Abstract: Cities are complex and constantly evolving systems where changing social needs have always reshaped the built environment. Considering recent evolutionary trends in housing emergencies, amplified by the COVID-19 pandemic, and environmental sustainability goals, a rethinking of the building heritage is fundamental. This article aims to promote the conversion of buildings designed initially for nonresidential uses as a process and project strategy based on energy efficiency and a holistic and integrated vision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Moreover, the negative association between digitization and CO 2 emissions uncovered by this study further accentuates the transformative potential of digitization in fostering energy efficiency and promoting sustainable practices. By offering empirical evidence of the favorable environmental outcomes associated with digitization, this research reinforces the significance of harnessing digital technologies to shape a greener and more sustainable future [103]. The findings also shed light on the role of industrial structure and urbanization in shaping carbon dioxide emissions.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, the negative association between digitization and CO 2 emissions uncovered by this study further accentuates the transformative potential of digitization in fostering energy efficiency and promoting sustainable practices. By offering empirical evidence of the favorable environmental outcomes associated with digitization, this research reinforces the significance of harnessing digital technologies to shape a greener and more sustainable future [103]. The findings also shed light on the role of industrial structure and urbanization in shaping carbon dioxide emissions.…”
Section: Discussionsupporting
confidence: 55%
“…Integrating GIS software and BIM models can save time and allow for more precise monitoring of construction and post-construction processes. Numerous studies have demonstrated the successful utilization of GIS software and BIM model integration for developing and visualizing a range of functions [70,71].…”
Section: Gis-bim Integrationmentioning
confidence: 99%
“…As for the project for disassembly and adaptability, it is a tool to be used in new buildings in order to promote the future reuse of the building, whether through the removal of its components or through adaptive reuse. In this case, disassembly avoids the extraction of resources for the production of new products [72], and adaptive reuse (ST14) promotes a new function for the existing park, optimizing land use and ensuring the updating of the building for new energy and energy requirements [73].…”
Section: Potential Applications Of Buildings As Materials Banks In Mi...mentioning
confidence: 99%